Peroxiredoxin post-translational modifications by redox messengers - Sylvie Riquier; Jacques Breton; Kahina Abbas; David Cornu; Cécile Bouton; Jean-Claude Drapier (Redox Biology, 2014)
Peroxiredoxins (Prxs) are a family of thiol peroxidases that participate in hydroperoxide detoxification and regulates H2O2 signaling. In mammals, the four typical 2-Cys Prxs (Prxs 1, 2, 3 and 4) are known to regulate H2O2-mediated intracellular signaling. The 2 catalytic cysteines of 2-Cys Prxs, the so-called peroxidatic and resolving cysteines, are regulatory switches that are prone to react with redox signaling molecules. We investigated the respective modifications induced by H2O2, NO and H2S in the murine macrophage cell line RAW264.7 by mass spectrometry and immunoblotting after separating 2-Cys Prxs by one-dimensional or two-dimensional PAGE. We found that H2S, unlike NO, does not prevent H2O2-mediated sulfinylation of 2-Cys Prxs and that Prx2 is more sensitive to NO-mediated protection against sulfinylation by peroxides. We also observed that cells exposed to exogenous NO, released by Cys-SNO or DETA-NO, or producing NO upon stimulation by IFN-γ and LPS, present an acidic form of Prx1 whose modification is consistent with S-homocysteinylation of its peroxidatic cysteine.